Optimizing DNA Analyses of Pangolin Products from the Trade for Species Identification in Vietnam - Thi Phuong Thanh, Bui; Thi Hanh, Ngo; Quang Truong, Nguyen; Duc Minh, Le (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 1, 2022)
To support law enforcement related to illegal wildlife trafficking in Vietnam, DNA analyses have been widely used to identify species based on products seized from the trade.  Pangolins are one of the most threatened mammal groups in Vietnam and across the world because they have been trafficked in huge numbers and considered the most traded mammals globally. Although the government and management agencies have implemented several deterrent measures to reduce the illicit trade of pangolins, a high number of violations with large seizures have still been detected in recent years in the country. Species identification of pangolin products is often challenging, as many products don’t have sufficient morphological diagnoses, especially their meat, hair, and scale. In this study, we present a protocol, which can be applied in laboratories in Vietnam, for extracting and amplifying a fragment of the mitochondrial cytochrome C oxidase subunit 1 ( COI ) from pangolin’s scales and hairs. This protocol was successfully employed to generate a fragment the COI gene from 10 confiscated pangolin samples. The results show for the first time that three samples originated from an African pangolin species and highlight the importance of applying molecular approaches to combating wildlife trafficking in Vietnam.